MON-LB109 Transcutaneous Magnetic Stimulation: A Novel Treatment of Diabetic Peripheral Neuropathy - Satyarengga, Medha (J Endocr Soc, 2020)
Objective: Transcutaneous Magnetic Stimulation (TCMS) is reported to be an effective treatment in multiple neurologic conditions such as migraine headaches, lower back pain, and post-traumatic peripheral neuropathic pain(1-3). The efficacy and safety of TCMS for diabetic peripheral neuropathy is not known. We evaluated whether TCMS is effective and safe in patients with diabetic peripheral neuropathy. Method: Eight patients with a previous diagnosis of diabetic peripheral neuropathy and baseline numerical pain-rating scale (NPRS) of 5 or greater in both feet were enrolled. NPRS scale was set from 0 to 10, 0 represents no pain and 10 representing the most severe pain. Each patient was treated with a single session of TCMS applied first on the plantar then the dorsal surface of both feet. Magnetic pulses (1.2 Tesla) were delivered every 6 seconds for 5 minutes in each foot on the plantar and dorsal surfaces, respectively. NPRS was repeated post-treatment over the course of 28-days follow-up period. Results: The mean baseline NPRS was 5.8 (± 1.0). Immediately post-treatment, mean NPRS improved to 1.3 (± 1.9), a 77.7 (± 36.5) % decrease. Mean NPRS at 7 and 28 days of follow-up was 2.9 (± 2.8) and 4.1 (± 3.3), respectively. These represent a 53.2(± 42.4) % improvement at 7 days and 30.5(±52.4) % improvement at 28 days of follow-up compared to baseline NPRS. None of the patients reported significant discomfort during the treatment, and no major side effects were observed during the study period. Conclusion: In this pilot study of patients with diabetic peripheral neuropathy, TCMS appears to be a safe and effective alternative in providing temporary pain relief. Longer and more frequent treatment sessions need to be explored to see if these can increase the effective duration. References: 1. Barker AT, Shields K. Transcranial Magnetic Stimulation: Basic Principles and Clinical Applications in Migraine. Headache. 2017 Mar;57(3):517-524. 2. Leung A, Fallah A, Shukla S. Transcutaneous Magnetic Stimulation (tMS) in Alleviating Post-Traumatic Peripheral Neuropathic Pain States: A Case Series. Pain Medicine. 2014 Jul; 15(7): 1196-1199. 3. Lim YH, Song JM, Choi EH, Lee JW. Effects of Repetitive Peripheral Magnetic Stimulation on Patients with Acute Low Back Pain: A Pilot Study. Ann Rehabil Med. 2018 Apr; 42(2): 229-238.